Early versus delayed emergency department presentation following mild Traumatic Brain Injury and the presence of symptom at 1, 4 and 12 weeks in children. Issue 6 (5th March 2020) - Gravel, Jocelyn; Ledoux, Andrée-Ann; Tang, Ken; Yeates, Keith Owens; Craig, William; Osmond, Martin; Boutis, Kathy; Burns, Emma; Sangha, Gurinder; Dubrovsky, Alexander Sasha; Beer, Darcy; Zemek, Roger
Abstract : Objectives: We evaluated the association between timing of presentation and postconcussive symptoms (PCS) at 1, 4 and 12 weeks after injury. Methods: This was a secondary analysis of a prospective cohort study conducted in nine Canadian paediatric EDs in 2013–2015 (5P study). Participants were children who suffered a head injury within the preceding 48 hours and met Zurich consensus concussion diagnostic criteria. The exposure was the time between head injury and ED presentation. The primary outcome was the presence of PCS at 1 week defined by the presence of at least three symptoms on the Post-Concussion Symptom Inventory (PCSI). Secondary outcomes evaluated PCS at 4 and 12 weeks. Multivariable logistic regression analyses were adjusted for ED PCSI and other potential confounders. Results: There were 3041 patients with a concussion in which timing of the injury was known. 2287 (75%) participants sought care in the first 12 hours, 388 (13%) 12–24 hours after trauma and 366 (12%) between 24 and 48 hours. Compared with children who sought care >24 hours after trauma, children who sought care in the first 12 hours had a significantly lower incidence of PCS at 1 week (OR: 0.55 (95% CI 0.41 to 0.75)) and 4 weeks (OR: 0.74 (95% CI 0.56 to 0.99)) but not at 12 weeks (OR: 0.88 (95% CI 0.63 to 1.23)). Conclusions: Patients who present early after a concussion appear to have a shorter duration of PCS than those presenting more than 12 hours later. Patients/families should be informed of the higher probability of PCS in children with delayed presentation.